VD_FINDINFO Séquestre / 2018 / 9 vom 25. Oktober 2018 - VD Tribunal cantonal (2018)
CAS DE SÉQUESTRE, RECONNAISSANCE DE LA DÉCISION, DÉCISION ÉTRANGÈRE | 271 al. 1 ch. 4 LP, 271 al. 1 ch. 6 LP, 272 al. 1 ch. 2 LP, 278 al. 3 LP, 32 CL (2007)